INNOVATIVE TECHNOLOGIES AS A FACTOR FOR THE FORMATION OF A HEALTHY LIFESTYLE OF CHILDREN - Pantyuk, Tetyana; Yarushak, Maria; Preys, Nataliya; Potuk, Sophia (Mountain School of Ukrainian Carpaty, 2019)
In the current conditions of society development, where dynamic processes take place in different areas of life, new requirements are being put forward for the formation of knowledge, skills of motivational tools and lifestyle of the individual. A special role in this process belongs to innovative technologies that are aimed at the development of various forms of thinking, creative abilities, and high social and adaptive capacities of the individual. In the current conditions of development of Ukrainian society, there is an urgent need to educate a healthy competitive individual, who possess developed intelligence, creative potential, striving for self-improvement and preservation of its own health. Today, many new technologies are introduced in Ukrainian education to improve learning, comprehensive harmonious development of children. The process of forming a healthy lifestyle is based on the child's own activity, and the result is achieved through innovative technologies: personal-oriented learning, cooperation and differentiation, project activity, art-therapeutic, pet therapy, portfolio, etc. Accordingly, the problem of training such a teacher who possesses the necessary professional competences, takes a step forward. Awareness of future teachers with a variety of innovative technologies and their successful adoption and use in practice will help to rethink the perspectives of school activities and work in the lives of students. The main driving force behind innovation is the teacher, as the subjective factor is crucial in the implementation and dissemination of innovations. The essence of health-preserving technologies lies in the comprehensive assessment of learning and upbringing conditions that make it possible to ensure the proper health of children, to care for their high level of self-realization, to develop healthy lifestyles, to monitor the indicators of the individual development of the child, and not only to predict changes in the health of children, but also apply appropriate psychological and pedagogical, corrective, rehabilitation measures to ensure the success of educational activities, improve quality of life for children with special educational needs, etc.